Analysis Semiotic of the Movie Siksa Neraka By Anggy Umbara (Semiotic Analysis of Charles Sanders Pierce) - Khafita, Khafita Aini; Ahmad Tamrin Sikumbang (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2024)
ABSTRACT The film can be used in preaching. This research aims to analyze the preaching messages in the movie "Siksa Neraka" by Anggy Umbara using Charles Sanders Peirce's semiotic approach. The research method used is qualitative. Data were analyzed through three main components: sign, object, and interpretant. The analysis results show that the film "Siksa Neraka" conveys various important preaching messages through visual symbolism and dialogue between characters. Some identified preaching messages include prohibitions against speaking harshly to parents, delaying prayers, inviting and committing sinful acts, committing adultery, cheating, gambling, slandering, and committing suicide. This film effectively conveys preaching values through the use of meaningful signs that can influence viewers to reflect on and improve their behavior. This research reveals how the film conveys moral messages and emphasizes the importance of visual media in educating and spreading religious values.   Keywords: Dakwah, Movie, Punishment, Hell